PERBANDINGAN EFEKTIVITAS NEFROPROTEKTOR EKSTRAK JINTAN HITAM (NIGELLA SATIVA) DENGAN EKSTRAK TEMULAWAK (CURCUMA XANTHORRHIZA) TERHADAP GAMBARAN HISTOPATOLOGI GINJAL TIKUS (RATTUS NOVERGICUS) YANG DIINDUKSI PARASETAMOL - KARTIKA HANDAYANI; DES SURYANI; HUMAIRAH MEDINA LIZA LUBIS (JURNAL ILMIAH MAKSITEK, 2021)
Over-use of paracetamol can cause nephrotoxicity. Black cumin and curcuma contain antioxidants that can ward off freeradicals produced by paracetamol metabolism. To compare the effectiveness of nephroprotector of black cumin extract andcurcuma extract on the histopathological picture of rats induced by paracetamol. True experimental, Post Test Only ControlDesign. 24 rats were divided into 4 groups: negative control standard diet and aquades, positive group paracetamol dose500 mg / kgBB, treatment 1 extract of black cumin extract 500 mg / kgBB, and treatment 2 curcuma extract 500 mg / kgBB.After 30 minutes P1 and P2 were given a dose of paracetamol 500 mg / kg. Rats were dissected for kidney removal andhistopathological preparations were made. Degeneration, necrosis and bleeding of the proximal tubules were assessed byscoring, comparison of scores between groups was assessed by the kruskal wallis test. There were nephroprotector effectsof black cumin and curcuma, with the same effectiveness on kidney damage induced by paracetamol. Black cumin can bedeveloped further as a nephroprotector.